Is Hba1c a Valuable Parameter in Non-Diabetic Patients with Peripheral Arterial Disease? - Senol, Sefa; Es, Mehmet Ugur; Akar, Ilker; Canbay, Zafer; Yuksel, Ahmet (Excerpta Medica Inc-Elsevier Science Inc, 2016)
[Abstract Not Available]
12th International Congress of Update in Cardiology and Cardiovascular Surgery -- MAR 10-13, 2016 -- Antalya, TURKEY